The Impact of Hybrid Quantum Learning Methods on Arabic Language Acquisition Among Students of Islamic Boarding School in Indonesia - Husna; Renaldi, Wildan; Sarehmasor, Tawfiq (Institut Agama Islam Negeri Palangka Raya, 2024)
The study explores Hybrid Quantum Learning in Arabic language education amid COVID-19, employing a quantitative approach with descriptive research methods. Data collection includes observation, interviews, tests, and questionnaires, analyzed through descriptive techniques and hypothesis testing. Experimental and control groups assess Hybrid Quantum-Classical Learning's efficacy, showing a 63.34% average difference in the former and 62.95% in the latter, indicating somewhat effective outcomes. Initially lacking, student engagement improved with model implementation. Further examination, supported by Likert scale responses, reveals an 87.33% satisfaction rate among students, highlighting the effectiveness of teaching auditory, visual, and kinesthetic skills in Arabic language education, particularly during the pandemic at Hasanka Islamic Boarding School in Indonesia.